COVID-19 Inpatient Deaths and Brought-in-Dead Cases in Malaysia - Lim, Poh Ying; Md Said, Salmiah; Kadir Shahar, Hayati; Azman, Ahmad Zaid Fattah; Mokhtar, Siti Aisah; Mahmud, Aidalina (Frontiers in Public Health, 2022)
COVID-19 mortality cases could be classified to two categories which are inpatient/hospital death and brought-in-death (BID), with the understanding of characteristics of BID cases is remained poor. Objective of this study is to explore the characteristics of 29,155 mortality cases, from Malaysia national data and compare the characteristics between inpatient death and BID group and the factors associated with high probability of BID, using multiple multilevel logistic regression model. Information of mortality cases from 16 different states in Malaysia, 17th March 2020 until 3rd November 2021 were be retrieved from open data introduced by Ministry of Health (MOH) with the collaboration with Ministry of Science, Technology & Innovation (MOSTI) and COVID-19 Immunisation Task Force (CITF). Among 29,155 COVID-19 mortality cases, 20.2% of mortality cases was BID (5,903). Decedents with aged 18-59, non-Malaysian, no comorbidity, not received vaccination before and 0-3days after confirmed to death was associated with higher probability to BID (p<0.05). A high prevalence of BID is an alarming public health issue has to pay increase attention. This study demonstrated that normal adult population are at high risk of BID compared to others. Hence, it is advisable to advocate awareness of monitoring all COVID-19 patients regularly, regardless age group and comorbidity status of patients to eschew bad consequences happened.